IMPLEMENTASI PENDEKATAN AGILE UNTUK PENGEMBANGAN OLAP DATA PENJUALAN - Wijaya, Andri; Maharani, Mutia; Meilinda (Universitas Lancang Kuning, 2024)
Sales data in large quantities are difficult to process and report using Microsoft Excel, which takes a long time. The proposed solution is to use Online Analytical Processing, a method that allows for faster decision-making through multidimensional data manipulation. In developing Online Analytical Processing for sales data, an agile approach is applied. With Online Analytical Processing, access to and display of transactional data becomes more efficient, improving analysis quality and supporting management decisions. Research results show that the prototype accelerates sales reports with a response time of 0.0039 seconds. Online Analytical Processing also facilitates decision-making in seconds. User Acceptance Testing results show high software quality and performance (100%), with an overall evaluation of 86,67% categorized as “Very Good”. Keywords: Sales Data, Online Analytical Processing, User Acceptance Testing, Agile Development